2019
DOI: 10.1016/j.biopsycho.2019.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Decreased prefrontal connectivity parallels cognitive fatigue-related performance decline after sleep deprivation. An optical imaging study

Abstract: Fatigue induced by sustained cognitive demands often entails decreased behavioural performance and the unavailability of brain resources, either due to reduced levels or impaired access. In the present study, we investigated the neural dynamics underlying preserved behavioural performance after inducing cognitive fatigue (CF) in a sleep deprivation (SD) condition in which resources are naturally compromised. Using functional near infrared spectroscopy (fNIRS), we recorded cortical brain activity during task-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 70 publications
3
33
0
Order By: Relevance
“…More recently, studies have emerged using the tools of cognitive neuroscience to investigate cognitive fatigue. While there is a growing body of literature using EEG 8 , 9 and optical imaging 10 to investigate fatigue, here we focus on the fMRI literature. Several fatigue-related brain areas have begun to emerge, include the striatum of the basal ganglia 3 , 11 13 , the ventro-medial prefrontal cortex (vmPFC; 13 15 ), the dorsal anterior cingulate cortex (dACC; 2 , 16 18 ), the dorsolateral prefrontal cortex (DLPFC; 2 , 17 , 19 ), and the anterior insula 2 , 13 , 17 , 20 , 21 .…”
Section: Introductionmentioning
confidence: 99%
“…More recently, studies have emerged using the tools of cognitive neuroscience to investigate cognitive fatigue. While there is a growing body of literature using EEG 8 , 9 and optical imaging 10 to investigate fatigue, here we focus on the fMRI literature. Several fatigue-related brain areas have begun to emerge, include the striatum of the basal ganglia 3 , 11 13 , the ventro-medial prefrontal cortex (vmPFC; 13 15 ), the dorsal anterior cingulate cortex (dACC; 2 , 16 18 ), the dorsolateral prefrontal cortex (DLPFC; 2 , 17 , 19 ), and the anterior insula 2 , 13 , 17 , 20 , 21 .…”
Section: Introductionmentioning
confidence: 99%
“…(e) the level of cognitive load [209][210][211][212], (f) the level of cognitive fatigue [213][214][215], (g) the influence of stress [216][217][218][219][220], (h) the influence of expertise level [104,122,212,221] or skill level [106,222], (i) training-related changes in motor-cognitive performance [105,117]. Accordingly, the provided evidence further buttresses the idea to use brain-derived parameters in exercise prescription.…”
Section: Advantages Of Brain-derived Indicators Of Internal Loadmentioning
confidence: 61%
“…However, these demands are mirrored in brain-derived measures. Regarding fNIRS-derived brain parameters, it was reported that they are sensitive to: the level of cognitive load [ 209 , 210 , 211 , 212 ], the level of cognitive fatigue [ 213 , 214 , 215 ], the influence of stress [ 216 , 217 , 218 , 219 , 220 ], the influence of expertise level [ 104 , 122 , 212 , 221 ] or skill level [ 106 , 222 ], training-related changes in motor–cognitive performance [ 105 , 117 ]. …”
Section: Advantages Of Brain-derived Indicators Of Internal Loadmentioning
confidence: 99%
“…For example, participants took sleepiness and empathy assessments multiple times in the SD condition but took these assessments only once in the RS condition. Recent advances showed that cognitive fatigue and sleepiness can be dissociated when accumulated sleep pressure is low [88]. Future studies should 3 further examine and control the confounding effect from cognitive fatigue in SD interactive learning.…”
Section: Limitationsmentioning
confidence: 99%